Novel Techniques to Reduce Transformer Inrush Current Using EMTP Software - Amir Ghaedi; Reza Sedaghati; Mehrdad Mahmoudian (مهندسی مخابرات جنوب)
Transformer inrush current is a high-amplitude, non-sinusoidal transient that occurs during initial energization, leading to voltage dips, power quality degradation, and relay misoperations. Unlike fault currents, inrush currents can be identified through harmonic analysis. Mitigating their amplitude is critical to avoiding these disruptions. This paper investigates novel inrush current mitigation techniques, with a focus on core magnetic materials. By evaluating their magnetic properties, we simulate the amplitude and harmonic composition of inrush current using EMTP-RV software. A comparative analysis identifies the most effective material for suppression. Additionally, alternative mitigation methods such as controlled energization timing, residual flux regulation, and transformer pre-loading are assessed. Their impact on inrush current is modeled in EMTP-RV, offering insights into optimal suppression strategies. The study aims to improve transformer reliability and power system stability by minimizing the adverse effects of inrush current.